Problematika Sholat Berjamaah di Dusun Seglagah Desa Sempu Kecamatan Ngebel Ponorogo - Andi Aprianto; Dewi Yunita Sari (Social Science Academic, 2025)
This study reveals that the Sempu community has low awareness of performing congregational prayers at the mosque. Although they realize that congregational prayers and the prosperity of the mosque are part of Islamic Development, in reality they do not do it. Therefore, to examine this, the author uses a PAR approach to reveal this. The formulation of the problem in this study focuses on two main aspects, namely how congregational prayers are implemented in Sempu Village, Ngebel District, Ponorogo Regency, and what obstacles the community faces in carrying them out. To answer this question, the author uses the theory of mentoring where the mentoring process involves a relationship between the mentor and the assisted party, where the mentor himself plays a role as a problem solver, encourages independence, and develops the potential of the assisted party. The research results show that the Seglagah Hamlet community still has a limited understanding of the procedures, virtues, and benefits of congregational prayer. Internal factors such as low individual awareness, laziness, and a lack of spiritual motivation are the dominant causes of community reluctance to attend the mosque. Furthermore, external factors such as busy work, environmental influences, and minimal social support also exacerbate this situation. Some people consider congregational prayer to take longer, so they prefer to pray alone at home. The lack of religious education and weak Islamic traditions in the surrounding community also contribute to low community participation. Thus, it can be concluded that internal and external factors influence each other in shaping community religious behavior. This study recommends efforts to increase religious awareness through religious education, spiritual guidance, and strengthening the role of religious leaders and Islamic institutions in society. These efforts are expected to foster motivation, broaden understanding, and encourage people to participate more actively in congregational prayers at mosques.